2019
DOI: 10.1590/1807-3107bor-2019.vol33.0014
|View full text |Cite
|
Sign up to set email alerts
|

Malocclusion and dental appearance in underprivileged Brazilian adolescents

Abstract: Satisfaction with dental aesthetics is a subjective indicator used in epidemiological studies and is related to health behaviours. Little is known about the factors that influence this indicator, particularly among adolescents who live in a situation of social vulnerability. The aim of this study was to investigate the relationship between malocclusion and dental appearance in underprivileged Brazilian adolescents. This analytical cross-sectional study was conducted in Piracicaba, Brazil, and evaluated 884 ado… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 31 publications
(44 reference statements)
2
16
0
1
Order By: Relevance
“…They observed that an increase in specific types of malocclusion was related to greater dissatisfaction with dental aesthetics. 43 Although the visual analogue scale (VAS) has limitations concerning content validity, the present study found high but similar VAS scores for expectations before and satisfaction after treatment for all aspects evaluated (chewing, aesthetics, phonetics and comfort). 46 A systematic review identified factors associated with treatment satisfaction of patients and caregivers, when applicable.…”
Section: Aesthetics and Satisfaction With Treatment And Servicessupporting
confidence: 55%
See 1 more Smart Citation
“…They observed that an increase in specific types of malocclusion was related to greater dissatisfaction with dental aesthetics. 43 Although the visual analogue scale (VAS) has limitations concerning content validity, the present study found high but similar VAS scores for expectations before and satisfaction after treatment for all aspects evaluated (chewing, aesthetics, phonetics and comfort). 46 A systematic review identified factors associated with treatment satisfaction of patients and caregivers, when applicable.…”
Section: Aesthetics and Satisfaction With Treatment And Servicessupporting
confidence: 55%
“…In addition, aesthetic changes resulting from treatment are considered an important indicator when judging the final treatment results. 42,43 Studies assessing satisfaction with aesthetics have confirmed that aesthetics is a key element for patients seeking dental treatment. Furthermore, studies have shown that patients with severe dental anxiety have less satisfaction with dental and facial appearance, and that the self-rating of orofacial aesthetics is related to both oral and psychological health.…”
Section: Aesthetics and Satisfaction With Treatment And Servicesmentioning
confidence: 99%
“…Hence, there is an increasing interest in studying the relationship between selfperceived malocclusion and orthodontic treatment need at this stage of life. [1][2][3]16,18,21,33,34 The study hypothesis was that occlusal changes in the smile and malocclusion severity levels would impact adolescents' esthetic concerns.…”
Section: Discussionmentioning
confidence: 99%
“…Dissatisfaction with dental esthetics is a subjective indicator related to behavioral problems in adoles-cence. [1][2][3] At that stage of life, malocclusion can be a trigger for psychological stress 4,5 due to shame, intimidation, and depression. [6][7][8] Individuals with low self-esteem are more likely to experience malocclusion-related adverse esthetic effects, [9][10][11] influencing social life, [12][13][14] and oral health-related quality of life.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation